Wheat Cost-Return Budget in Western Kansas - Dumler, Troy J.; O'Brien, Daniel M. (My University, 2012)
This publication projects a budget that reflects expected income and costs based on typical production of wheat in western Kansas.
MF903_2012_12
Keywords: MF920; Economics; Crops; MF